The effect of capital intensity and institutional ownership on tax avoidance, with gender diversity as a moderating variable - Nada Asyfa; Suparna Wijaya (WIM Solusi Prima, 2026)
This study aims to analyze the effect of capital intensity and institutional ownership on tax avoidance, and to examine the role of gender diversity as a moderating variable in banking sub-sector companies listed on the Indonesia Stock Exchange for the 2020–2024 period. Tax avoidance is proxied by the Cash Effective Tax Rate (CETR), while capital intensity is measured by the ratio of fixed assets to total assets and institutional ownership by the percentage of shares held by institutions. Gender diversity is measured by the ratio of female directors to the total number of board members, with liquidity as a control variable. This study employs a quantitative approach using panel data regression on 214 observations selected through purposive sampling, processed with STATA 17, in which the Fixed Effects Model was selected as the estimation model with robust standard errors correction. The results show that capital intensity has a positive and significant effect on tax avoidance, whereas institutional ownership has no significant effect. Gender diversity is proven to moderate and weaken the effect of capital intensity on tax avoidance, but it cannot moderate the relationship between institutional ownership and tax avoidance. These findings imply that fixed-asset characteristics play a greater role in influencing corporate tax strategies, while the presence of women on the board of directors can enhance prudence and internal oversight of tax policy in capital-intensive firms. This study is expected to contribute empirically to the tax accounting literature and serve as a reference for regulators and practitioners in formulating tax policies and corporate governance practices.